Application of Biochar and Biofertilizer Combination on Corn in Up Land Pandeglang Regency: Aplikasi Kombinasi Biochar dan Pupuk Hayati pada Tanaman Jagung di Lahan Kering Kabupaten Pandeglang - Dhanti Hanifa Muslimah; Widyastuti, Rahayu; Djajakirana, Gunawan (Jurnal Ilmu Tanah dan Lingkungan, 2022)
Biochar is an alternative amendment for improving soil is to rehabilitate degraded land, especially dry land. In addition, biochar serves as a habitat for soil microbes that play an important role in the availability of nutrients for plants. The use of biofertilizers in agriculture is part of the support for sustainable agriculture because it is environmentally friendly. This study aimed to examine effect of application biochar and biofertilizers combination on chemical and biological properties of soil as well as growth and yield of maize in an up land, Pandeglang Regency. The experimental design in this study was a factorial completely randomized design with two factors. The first factor was biochar with 3 levels (0; 2.5; 5 tons ha-1) and the second factor was combination of  biofertilizer (PHC) and NPK with 5 types (100% PHC, 100% NPK, 25% PHC + 75% NPK, 50% PHC + 50% NPK, and 75% PHC + 25% NPK). Each treatment was replicated 3 times so there were 45 experimental units. The results of this study showed that the application of biochar dose of 5 tons ha-1 (B2) significantly increased K-available in soil and plant height. The combination of 75% biofertilizer and 25% NPK (P4) significantly increased the population of N2-fixing bacteria and cellulolytic bacteria. The combination of biochar dose 2 with 100% NPK fertilizer (B2P1) is the best treatment combination in improving soil nutrient status. On the other hand, the combination of application of biochar dose 1 (2.5 ton ha-1) with 50:50 concentration of biofertilizer and NPK (B1P3) has the opportunity to support the growth and yield of maize.